PENGARUH PROMOSI, E-WOM, DAN BRAND IMAGE TERHADAP NIAT BERKUNJUNG KEMBALI PADA KONSUMEN OUTBACK UBUD ADVENTURE - Pramanaputra, Wayan Dede Arya; Santika, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.04.TAHUN.2023, 2023)
Outback Ubud Adventure needs to pay attention to the information needed by consumers, because if consumers are satisfied with information about the company, it will affect consumers to have the re-visit intention to return to the tourist attraction. Destination from study this for explain the effect of promotion, e - WOM, and brand image on re-visit intention again to Outback Ubud Adventures. Study this done in Outback Ubud Adventures. Samples taken as many as 100 respondents through non- probability sampling method with purposive sampling technique and distributed use questionnaire google forms with criteria that have been customized, measured with 20 indicators and using scale likert. Data analysis techniques used is analysis statistics descriptive, test assumptions classic, analysis multiple linear regression, model accuracy test and testing hypothesis. Result of study this show that whole hypothesis accepted. Promotion take effect by positive and significant to re-visit intention, eWOM take effect by positive and significant to re-visit intention, brand image is influential by positive and significant to re-visit intention.